Peer Group Support Dalam Meningkatkan Pengetahuan Dan Sikap Ibu Hamil Tentang Preeklampsia - Mersha Eky P; Mira Triharini; Tiyas Kusumaningrum (Universitas Airlangga, 2014)
Preeclampsia is disease by signs hypertension, oedema and proteinuria that arises because of pregnancy. Sudspreeclampsia lightly with hypertension, edema and proteinuria often unknown or not cared by a pregnant mother relatedso unwittingly in no time can arise preeklampsia heavy even eclampsia. Peer group support is support peers namely bygranting information, aid, or material obtained from their peers a familiar.The purpose of this research is to analyzeinfluence peer group support against knowledge and attitude pregnant women about preeclampsia. This research usesthe pre-experimental design. The population was pregnant women with gestational age of at least trimester II in theregion work Health Center of Candi. The sample was selected using a purposive sampling technique. Its independentvariable is a peer support group, and the variable dependennya is the knowledge and attitude of pregnant women. TheData collected by using questionnaire and results were tested using the Wilcoxon Signed Rank Test with alpha ≤ 0.05.The results indicate that this method can improve the knowledge demonstrated by the value of significance p = 0.007 andchange a positive attitude with a value of significance p = 0.005. For nursing the child, maternitas and Health Clinics inthe community are expected to implement the activities of peer group support in an attempt to increase the knowledgeand attitude to pregnant women about preeklampsia. Researchers can then use more samples or giving the control groupto obtain a more representative results and modify the method by means of increasing the intensity of the meetings.